Decreased retention of olfactory predator recognition in juvenile surgeon fish exposed to pesticide. (October 2018) - Bertucci, Frédéric; Jacob, Hugo; Mignucci, Alexandre; Gache, Camille; Roux, Natacha; Besson, Marc; Berthe, Cécile; Metian, Marc; Lecchini, David
Abstract: Dory, the animated surgeonfish created by the Pixar Animation studios, famously suffered from short-term memory loss leading to many adventures. In reality, many fishes have excellent cognitive abilities and are able to learn and retain important information such as the identity of predators. However, if and how cognition can be affected by anthropogenically altered oceanic conditions is poorly understood. Here, we examine the effect of a widely used pesticide, chlorpyrifos, on the retention of acquired predator recognition in post-larval stage of the surgeonfish Acanthurus triostegus . Through associative learning, post-larvae of A. triostegus were first observed to forage significantly less in the presence of conspecific alarm cues and alarm cues associated to a predator's odor. The retention of this anti-predator behavior was estimated to last between 2 and 5 days in the absence of pesticide. However, environmentally-relevant concentrations of chlorpyrifos (1 μg.L −1 ) induced the loss of this acquired predator recognition. This reduced ability to recognize learned predators is discussed as it may lead to more vulnerable fish communities in coastal areas subjected to organophosphate pesticide pollution. Highlights: Coral reefs face many threats such as ocean warming, acidification and pollution. No studies examined how chemicals affect the cognitive abilities of reef organisms. This study investigated anti-predator behavior in post-larval Acanthurus triostegus . This behavior was retained between 2 and 5 days in the absence of pesticide. The pesticide Chlorpyrifos induced a loss of this crucial information.